Layanan Pengembangan Diri Di SD Al Islam 2 Jamsaren Surakarta - Listyani, Ongky Alif; , Drs. Rubino Rubiyanto, M.Pd (2017)
This study aims to describe 1) the implementation of self-development services khsusnya on the guidance of learning and emotional intelligence in SD Al Islam 2 Jamsaren Surakarta, 2) Techniques / ways of self-development services, especially on the guidance of learning and emotional intelligence in SD Al Islam 2 Jamsaren Surakarta and 3 ) Impact / results of self-development services especially on the guidance of learning and emotional intelligence in SD Al Islam 2 Jamsaren Surakarta. This research uses qualitative research type. Data collection techniques with observation, interview and documentation. Data validity with triangulation. Data were analyzed interactively. The results of the study showed that 1) self-development services, especially on the guidance of learning and emotional intelligence: the cooperation of the guardian and teacher, self-development is taught in accordance with Al Quran and Hadith. 2)Techniques / ways to provide self-development services, especially on the guidance of learning and emotional intelligence Ie Identify and understand the problem of students on the subject matter that is considered difficult after that students grouped into 5-6 groups, when students in groups of teachers help students in solving problems on subjects that are considered difficult accompanied by motivation, advice and stories based on Hadith and the Qur'an. 3) The impact of self-development services there are positive impacts that students can change better according to expectations of teachers and schools, student achievement increases, students are more confident and able to control emotions, emotional maturity is fitting, students more enthusiasm and easy to compete positively with his friend And there are negative impacts that the difficulty of cooperation from the school and home parties.